Research on Soft Rocks for the Construction of Roadbeds for High-Speed Railroad: Effect of Water Soaking Environment - Xiangdong Zhang; Jie Geng; Yuebo Xu; Zhongchao Zhou; Shuai Pang (Advances in Materials Science and Engineering)
The strength of the roadbed composed of soft rock decreases following water immersion. Cement slurry is mixed with a soft rock to strengthen the soft rock roadbed to address this problem. The uniaxial compressive strength was determined, and the triaxial compression tests were conducted to analyze muddy sandstones mixed with different amounts of the cement slurry of the same composition. Some of the cured samples were soaked in water, and the samples were analyzed. The results were compared with the results obtained by analyzing unsoaked samples. The MIDAS/GTS NX software was used to develop a three-dimensional finite model to simulate the settlement patterns of roadbeds developed in the presence of natural water, saturated water, and muddy sandstone reinforcements. The experimental results have been presented and discussed. (1) When the filling rate corresponding to the cement slurry is 32%, the uniaxial compressive strength of muddy sandstone containing natural water reaches 3.32 MPa, which is approximately 5 times higher than the strength of muddy sandstone devoid of cement slurry. (2) The water absorption energy of the reinforced muddy sandstone was analyzed from the perspective of saturated water content. The water plugging effect observed after the addition of the cement slurry was studied, and the equations defining uniaxial compressive strength, elastic modulus, and free saturated water content were established. (3) An increase in the content of the cement slurry admixture resulted in a change in the nature of the partial stress–strain curves generated for muddy sandstone. The curve change from strain-hardening to strain-softening type and the deformation modulus and extent of cohesion realized increased exponentially with an increase in the cement slurry filling rate. A positive linear correlation was observed between the internal friction angle and the cement slurry filling rate. (4) An increase in the cement slurry filling rate corresponding to the saturated muddy sandstone resulted in an exponential decrease in the settlement deformation value. The vertical displacement decreased to 0.3497 mm when the grouting rate reached 32% under conditions of saturation. The deformation tended to converge and stabilize, indicating that the introduction of the admixture consisting of the cement slurry could help in effectively controlling the property of settlement deformation observed in the fully weathered muddy sandstone roadbed. The results helped in the scientific evaluation of the reinforcement effect. The reported results also helped develop a theoretical basis for the development of soft foundation reinforcement.